CYTOCHEMICAL STUDIES OF MITOCHONDRIA : II. ENZYMES ASSOCIATED WITH A MITOCHONDRIAL MEMBRANE FRACTION - Siekevitz, Philip (The Rockefeller University Press, 1956)
1. Mitochondria isolated from rat liver were disrupted with 0.3 per cent deoxycholate and a number of subfractions were isolated from this preparation by differential centrifugation. 2. The protein N, RNA and phospholipide content, as well as the succinoxidase, cytochrome c oxidase, adenylate kinase, and DPNH-cytochrome c reductase of these fractions were determined. 3. Two of these subfractions, found to consist of mitochondrial membranes (2), contained ∼ 12 per cent of the protein N and ∼ 35 per cent of the phospholipide of the whole mitochondria and accounted for ∼ 70 per cent of the succinoxidase and cytochrome c oxidase activity of the original mitochondrial preparation. There was no discernible adenylate kinase, DPNH-cytochrome c reductase, or phosphorylating activities in these fractions, nor could they oxidize other substrates of the Krebs's cycle. 4. The most active fraction (60 minutes at 105,000 g pellet) had a higher phospholipide/protein value than the whole mitochondria and showed a seven-to elevenfold concentration of succinoxidase and cytochrome c oxidase activities. 5. Evidence has been given to indicate that the various components of the succinoxidase complex are present in this membrane fraction in the same relative proportions as in the whole mitochondria. 6. The implications of these findings are discussed.